Optimization of controlled low strength concrete using GGBS, PFA and limestone dust - Gupta, Ram (My University, 2013)
A Controlled Low Strength Material (CLSM) is a highly flowable self-compacting material which is primarily composed of sand, cement, water and other filler materials. It is principally used as a replacement for soil backfill. The purpose of this project was to optimise the mixture proportions for performance using various fillers and cementitious materials such as GGBS, PFA and limestone dust. The recycling of these waste materials contributes to construction sustainability. The mixes must possess the consistency, flowability and strength which is required for CLSM. This was achieved through trial mixing, where derivation of new mixes is based on the performance of previous pours. To investigate the performance of the mixes derived, tests for flowability, density and compressive strength were carried out. It was found that the cement/GGBS CLSM mixes could not demonstrate the highly flowable and consistent mixes with high water/fines to achieve the required low strength of not more than 2MPA at 28-days. To rectify this, ternary mixes were derived by incorporating PFA and limestone dust with cement/GGBS mix. The optimum pour with regards to both fresh and hardened properties was found to be the cement/GGBS/limestone dust, which consisted of the lowest cement contents in the range of 15 – 20 kg/m3. By replacing the sand content with an appropriate content of PFA or limestone dust, an improvement in the flowability of the pours was achieved. The cement/GGBS/PFA mixes did not comply with the hardened state properties as PFA contributed in long-term strength.
Master of Engineering (Structural Engineering), Thesis
Keywords: GGBS; PFA; LIMESTONE DUST; CLSM; CONCRETE